2018
DOI: 10.1111/neup.12511
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomatous meningioma: A metaplastic or degenerative phenomenon?

Abstract: Xanthomatous changes can be observed in various conditions including primary xanthomatosis that is linked to an underlying hypercholesterolemia and more commonly associated with secondary xanthomatous degenerative processes in neoplasm and chronic inflammation. Meningioma with extensive xanthomatous change is exceedingly rare. The presence of cholesterol clefts within this peculiar meningioma subtype has not been described. Herein, we report an unusual case of xanthomatous meningioma in an 83-year-old normolip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…[ 10 11 ] The persistence of the meningothelial immunohistochemistry profile suggests that xanthomatous change is not true histiocytic metaplasia but rather a degenerative process which occurs in the central portion of the tumor, which is poorly nourished. [ 12 ] Further studies are required to elucidate which of these competing points of view are correct.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 ] The persistence of the meningothelial immunohistochemistry profile suggests that xanthomatous change is not true histiocytic metaplasia but rather a degenerative process which occurs in the central portion of the tumor, which is poorly nourished. [ 12 ] Further studies are required to elucidate which of these competing points of view are correct.…”
Section: Discussionmentioning
confidence: 99%
“…10 The tumor is reported in a wide range of age group from children to elderly patients and can be localized in supratentorial or infratentorial regions without any specific predilection (6) (Table 1). [2][3][4][5][6][7][8][9][10][11][12][13] On MRIs of the brain, these metasplatic meningiomas are usually iso-to hypointense on T1 and iso-to hyperintense on T2 weighted MRI. Katayama et al reported evidence of hyperintense lobules on both T1 and T2 weighted MRI images, and hypodensity on CT of the brain in xanthomatous meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Meningothelial and transitional variants often show fat accumulation whereas neoplastic cells in xanthomatous meningiomas are filled up with lipids appearing as foamy cell with cholesterol clefts (Figure 2C). 2 Macrophages surround these neoplastic transformed cells, hence it is essential to carefully establish the origin of these xanthomatous cells. Xanthomatous meningioma does not show inflammation and is different from xanthogranulomatous inflammatory changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations